2021
DOI: 10.15244/pjoes/126320
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution Characteristics of Outdoor Particles Concentrations in High-Rise Buildings

Abstract: With speeding up urbanization in China, it is important to understand the vertical distribution characteristics of outdoor particulate matter concentrations of high-rise buildings. A high-rise building at different heights (1 st , 7 th , 11 th , 17 th , 23 th , and 27 th floors) in a university in Xi'an was tested and analyzed in this paper. Test time was 8:00, 12:00, 15:00, 15:00 and 22:00, respectively. The results showed that the concentration of each particulate matter changed the same trend roughly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…According to Table 2 ’s data, particles from 0 to 2.5 μm accounted for the majority of the atmosphere (approximately 99.88%); particles from 0 to 1.0 μm accounted for 99.55%. The atmospheric particles in Xi’an were mainly small particles; this was consistent with conclusions in relevant research [ 34 ]. These particles increase health risks [ 35 ]; thus, improving air filters’ purification effect is urgent.…”
Section: Resultssupporting
confidence: 91%
“…According to Table 2 ’s data, particles from 0 to 2.5 μm accounted for the majority of the atmosphere (approximately 99.88%); particles from 0 to 1.0 μm accounted for 99.55%. The atmospheric particles in Xi’an were mainly small particles; this was consistent with conclusions in relevant research [ 34 ]. These particles increase health risks [ 35 ]; thus, improving air filters’ purification effect is urgent.…”
Section: Resultssupporting
confidence: 91%
“…The particle sizes of 0~1.0μm accounted for more than 99.7%. Particles in the atmosphere in Xi'an were mainly small in size, which was easy to enter the human respiratory tract and lungs, it is consistent with the conclusion of the literature [4,33]. Therefore, it is very necessary to effectively filter and purify the particulate matter in the fresh air system.…”
Section: Resultssupporting
confidence: 81%
“…With the increasing of air pollution and the improvement of building air-tightness levels in recent years, indoor air pollution problems have become increasingly prominent [1,2]. It was not only seriously affected people's normal life, such as bad living conditions and unsatisfactory living feelings [3,4], but also brought many diseases to people's physical and mental health [5,6]. Relevant literature had shown that particles of different sizes would enter different parts of the human body and they could cause varying degrees of damage [7], as showed in fig.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that particles of sizes of 0−2.5 μm comprised most of the atmosphere, about 99.68%, of which the particles of sizes of 0− 1.0 μm accounted for 98.96%. It is clear that in Xi'an, particles are mainly composed of fine particles; 39 such particles can easily enter the respiratory tract and lungs of the human body, leading to disease and death. 40 Therefore, the purification effect of fine particles should be improved to achieve the purpose of creating good indoor environmental hygiene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%